Defining and measuring sustainability : the biogeophysical foundations - Munasinghe, Mohan, 1945-; Shearer, Walter (Washington, D.C. : Distributed for the United Nations University by the World Bank, 1995)
Presents the highlights of the June 1992 United Nations Conference on Environment and Development which resulted in the Rio Declaration, Agenda 21, and the UN Commission on Sustainable Development.
Includes bibliographical references.
oif 14/09/15
Loan
Keywords: Natural resources -- Management; Sustainable development; Sustainable development -- Case studies